Analisa Penerapan Metode OCRA Pada Pertukaran Mahasiswa Dalam Mendukung Kampus Merdeka Dengan Pembobotan ROC - Siregar, Tesa Aurelia (CV. Graha Mitra Edukasi, 2022)
The independent campus is one of the programs from the policy of the ministry of education and culture that has been approved by the president to motivate students to improve their abilities by participating in learning activities carried out for one or up to three semesters according to interests outside the study program or college, where students follow the lesson. However, in the selection of student exchanges in support of independent campuses, there are often problems, namely the student section is confused in determining it because of the large amount of data that does not meet the criteria but has already registered. So in this study, a decision support system is needed as a system for determining eligible students in an independent campus exchange. As for the selection of student exchanges in supporting an independent campus, there are five criteria including GPA, non-academic achievements, skills, ethics and academic sanctions. So with this, a decision support system is urgently needed to solve problems using the ROC (Rank Order Centroid) and OCRA (Operational Competitiveness Rating Analysis) methods which will produce weight values ​​for each criterion and preference values ​​from the first ranking alternative. So that the chosen one in the selection of the independent campus student exchange is Alternative A1, namely Tasya Salsabilla with a value of 1,071.